Dwarfism arts and advocacy : creating our own positive identity - Pritchard, Erin (Emerald Publishing Limited, 2024)
When you think of a person with dwarfism, what image springs to mind? Now, hold onto that image and consider how you are expected to respond to it. Is your response laughter, amusement or maybe curiosity? Do you even see them as human, or just a novelty for the entertainment of others? Rectifying the lack of representation of dwarfism in Disability arts, Dwarfism Arts and Advocacy brings together leading activists, both academics and arts practitioners with lived experience of dwarfism, to raise awareness within academia and society and challenge ableist representations of people with dwarfism. Raising a collective voice, authors offer their thoughts, experiences and, most importantly, recommendations for improving representations of dwarfism and counteracting ableist attitudes both in popular media and in everyday life. Disputing derogatory representations of this condition, Dwarfism Arts and Advocacy opens up a new avenue for disability studies, encouraging advocacy and challenging able-bodied readers to re-examine their perceptions of this community.
Keywords: Dwarfs (Persons); People with disabilities and the arts.; Activism.; Identity (Philosophical concept); Social Science -- People with Disabilities.; Political activism -- Political engagement.; Disability: social aspects.; elektronické knihy; electronic books